Struvite formation and control in wastewater treatment - Doyle, J. D. (Cranfield University, 2002)
Struvite causes maintenance, and operational problems due to fouling in wastewater and sludge treatment systems. Struvite formation was initially investigated using a series of jar tests on real and synthetic sludge liquors. A computer model predicting struvite precipitation potential was compared to the results generated. Struvite formation was found to be closely linked to pH with increasing pH resulting in decreasing struvite solubility. Further studies analysed the relationship between a solutions' supersaturation ratio, material and the scaling rate. Tests were undertaken at 3 supersaturation ratios with 3 different materials: stainless steel, Teflon and acrylic. Acrylic and Teflon coupons were scientifically roughened to show the influence that surface roughness has on a materials' scaling propensity. The control of struvite precipitation was investigated using a range of chemical inhibitors and chelating agents. Experiments using the same materials used previously were performed with a range of scale inhibitors and chelating agents. The scale inhibitors did not prevent struvite from forming, with only one product, Polystabilis, showing a reduction in the mass of scale formed on the impellers. Of the chelating agents tested, EDTA was the most effective even in alkaline conditions and was shown to have the ability to re-dissolve struvite previously formed on materials.